Using Waste Limestone Powder as Filler in a Toxic Epoxy Resin Coating and Its Influence on Adhesive Properties - Agnieszka Chowaniec (AIDIC Servizi S.r.l., 2021)
Epoxy resin is very harmful to the environment, e.g. it affects aquatic organisms, irritates the skin and eyes and causes allergic reactions. Because, the epoxy resin is an expensive building material, this study presents research on reducing its mass needed to make a floor coating, through the use of waste limestone powder as a filler. This additionally supports the recycling of the mineral waste. The main aim of the research was to find the amount of waste limestone powder that would not adversely affect the adhesive properties of the epoxy resin coating. The tests were carried out on a concrete element, with two differently prepared substrate surfaces using grinding and left raw after concreting. The epoxy resin coating contained waste limestone powder in an amount of 0 to 29% was examined. The pull-off strength of the coating was examined at three points for each coating composition on both types of the surfaces. The aim of the research was achieved by obtaining the satisfactory results of the pull-off strength for epoxy resin filled with the waste limestone powder.